2017
DOI: 10.1038/cddis.2017.549
|View full text |Cite
|
Sign up to set email alerts
|

Ly6G+ neutrophil-derived miR-223 inhibits the NLRP3 inflammasome in mitochondrial DAMP-induced acute lung injury

Abstract: MicroRNA (miRNA) mediates RNA interference to regulate a variety of innate immune processes, but how miRNAs coordinate the mechanisms underlying acute lung injury/acute respiratory distress syndrome (ALI/ARDS) in patients with pulmonary inflammatory injury is still unknown. In this study, we demonstrated that miR-223 limits the number of Ly6G+ neutrophils and inhibits the activity of the NLRP3 inflammasome to alleviate ALI induced by mitochondrial damage-associated molecular patterns (DAMPs) (MTDs). miR-223 ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
62
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(70 citation statements)
references
References 56 publications
7
62
0
1
Order By: Relevance
“…PI3K/AKT pathway plays an important biological role in cell apoptosis, survival, proliferation, cytoskeleton change and other biological processes [32]. It has been proved that the PI3K/AKT signalling pathway participates in the regulation of the pathological process of cerebral ischemia injury [33][34][35]. In addition, several studies have reported that Nrf2 is a downstream regulator of PI3K/AKT pathway [18,36].…”
Section: Discussionmentioning
confidence: 99%
“…PI3K/AKT pathway plays an important biological role in cell apoptosis, survival, proliferation, cytoskeleton change and other biological processes [32]. It has been proved that the PI3K/AKT signalling pathway participates in the regulation of the pathological process of cerebral ischemia injury [33][34][35]. In addition, several studies have reported that Nrf2 is a downstream regulator of PI3K/AKT pathway [18,36].…”
Section: Discussionmentioning
confidence: 99%
“…Evidence from murine lung injury models and ARDS patient samples emphasize the role of the NLRP3 inflammasome in the pathogenesis and detrimental outcome of ARDS [20,21]. In keeping with this, the coronavirus ORF3a protein has been shown to induce NLRP3 inflammasome activity [22].…”
Section: Main Textmentioning
confidence: 90%
“…Furthermore, miR‐223 is expressed stably at high levels in neutrophils and overexpression of miR‐223 was shown to diminish NLR family pyrin domain containing 3 (NLRP3) inflammasome activity via direct targeting of NLRP3 and in turn dampens NLRP3‐dependent IL‐1β production . The NLRP3‐miR‐223 axis was further studied in acute lung injury (ALI) . Patients with acute respiratory distress syndrome (ARDS) caused by trauma and blood transfusion showed high level of miR‐223 in the bronchial alveolar lavage fluid (BALF) when compared with health controls.…”
Section: Mir‐223 In Innate Immunitymentioning
confidence: 99%
“…49 The NLRP3-miR-223 axis was further studied in acute lung injury (ALI). 50 Patients with acute respiratory distress syndrome (ARDS) caused by trauma and blood transfusion showed high level of miR-223 in the bronchial alveolar lavage fluid (BALF) when compared with health controls. In ALI induced by mitochondrial damage-associated molecular patterns (DAMPs) (MTDs), miR-223 −/+ mice experienced decreased arterial oxygen partial pressure to fractional inspired oxygen ratio (PaO 2 /FiO 2 ), increased lung wet to dry ratio, and elevated infiltrating cells to the airway.…”
Section: Mir-223 In the Regulation Of Neutrophil Functionmentioning
confidence: 99%